Letter - Vansittart, Robert Gilbert Vansittart, Baron, 1881-1957
023_0025_001 FOREIGN OFFICE, S.W.1. 7th December, 1936. Many thanks for your letter of November 30th and for the information enclosed therein on the subject of the transport of war material to Spanish rebels. I hope you will forgive my delay in answering your letter, my reason being that I was desirous of comparing the information you were kind enough to send me with that which was or might become available from our own sources. I have now completed my enquiries, so perhaps when you are passing in this direction one day, you will look in on me and we could have a talk on the whole question. Yours sincerely Robert Vansittart Sir Walter Citrine, K.B.E., Transport House, Smith Square, S.W.1. 292/946/23/28